Late Palaeozoic 40Ar/39Ar ages of the HP-LT metamorphic rocks from the Kekesu Valley, Chinese southwestern Tianshan: new constraints on exhumation tectonics. Issue 4 (11th March 2016) - Xia, Bin; Zhang, Lifei; Bader, Thomas; Shen, Tingting; Chen, Nengsong
Abstract: Although numerous ages have been obtained for the Chinese southwestern Tianshan high pressure/ultrahigh pressure-low temperature (HP/UHP-LT) metamorphic belt in the past two decades, its exhumation history is still controversial. The poor age constraint was related to the appealing low metamorphic temperatures and excess Ar commonly present under HP/UHP conditions. This study aims to provide new age constraints on the orogen's exhumation by obtaining 40 Ar/ 39 Ar mica ages using the conventional step-heating technique, with emphasis on the avoidance of excess Ar contamination. From a cross section along the Kekesu Valley, four samples, three from the HP-LT metamorphic belt (TK050, TK051, and TK081) and one from the southern margin of the low pressure metamorphic belt (TK097), were selected for 40 Ar/ 39 Ar dating. Phengites from garnet glaucophane schist TK050 and the surrounding rock garnet phengite schist TK051 yield comparable plateau ages of 321.4 ± 1.6 and 318.6 ± 1.6 Ma, respectively, while epidote mica schist TK081 gives a younger plateau age of 293.3 ± 1.5 Ma. Considering the chemical compositions of phengites, mineral assemblages, and microstructures in the thin slices, we suppose that the former represents the time the HP rocks retrograded from the peak stage (eclogite facies) to the (epidote)-blueschist facies, whereas the latter reflects greenschist facies overprinting. Biotite and muscovite from two-mica quartzite TK097 give similar plateau ages of 253.0 ± 1.3 and 247.1 ± 1.2 Ma, interpreted to date movement on the post collisional transcrustal South Nalati ductile shear zone. By combining our new ages with published data, a two-stage exhumation model is suggested for the Chinese southwestern Tianshan HP/UHP-LT metamorphic belt: initial fast exhumation to a depth of about 30–35 km by 320 Ma was followed by relatively slow ( 1 mm year –1 ) uplift to 10 km by 293 Ma.